Computational methods. Euler-lagrange methods (2016)
The Eulerian approach for the particles considers cellaveraged particle characteristics based on the continuous-phase grid nodes. This approach is efficient in terms of predicting particle concentration. Lagrangian Particle Equation of Motion Since the dispersed phase is treated in terms of individual particle paths, the Lagrangian method is also sometimes referred to as the "discrete" approach. Particle velocity vectors in different reference frames in the context of an Eulerian continuous-phase grid: Lagrangian vectors based on particle positions and Eulerian particle velocity vectors based on average over a control volume centered at a discrete grid node used to store fluid properties and particle properties and particle properties. Once the Eulerian conservation equations are discretized, each node in the computational domain will include cell-averaged particle-phase variables. While continuous-flow computational fluid dynamics formulations are generally considered in an Eulerian reference, the dispersed-phase characteristics. This difference of the reference frame for dispersed phase is the key division between the different multiphase numerical methods.